Vascular Endothelial Growth FactorC Serum and Endostatin Serum as Predictors of Lympho Vascular Invasion in Early Stage Cervical Cancer - Rusmardiani, Andhinna; Rauf, Syahrul; Lukas, Efendi (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the relationship of Vascular Endothelial Growth Factors-C (VEGF-C), endostatin and the ratio of VEGF-C/ endostatin with limfo vascular invasion in patient with early stage cervical cancer. Methods: This study used a cross sectional method. Samples were all patients with early stage cervical cancer who came to the several teaching hospitals of Obstetrics and Gynecology Department Universitas Hasanuddin Medical Faculty that meet the criteria, then we measured the levels of VEGF-C and endostatin. Results: We get 30 women with cervical carcinoma. The results showed that the serum levels of VEGF-C was higher in limfo vascular invasion positive (p = 0.017); the ratio of VEGF-C/ endostatin higher in limfo vascular invasion positive (p = 0.004); whereas serum levels of endostatin did not differ significantly in limfo vascular invasion positive or negative (p = 0.522). Conclusion: The level of VEGF-C and VEGF-C/ endostatin ratio was higher in patients with early stage cervical cancer with positive LVSI than negative LVSI. [Indones J Obstet Gynecol 2017; 5-2: 105-109] Keywords: cervix uteri cancer, endostatin, limfo vascular invasion, VEGF-C